Single-dose Intravenous Injection Toxicity of Watersoluble Danggui Pharmacopuncture (WDP) in Sprague-Dawley Rats - Sunju Park; Hae-Mo Park; Seung-Ho Sun (Journal of Pharmacopuncture, 2018)
Objective:This study is to evaluate both the single-dose intravenous injection toxicity and the approximate lethal dose of Water-soluble Danggui Pharmacopuncture (WDP) in Sprague-Dawley (SD) rats. Methods: Toxicity experiments were conducted at Good Laboratory Practice (GLP) laboratory in Biotoxtech Co., according to the regulations of GLP. WDP injection of dose 0.125, 0.25, and 0.5 mL/animal were experimental groups and normal saline injection group was control group. WDP and normal saline were injected once to 6- week old 5 male and 5 female SD rats at the tail veins at approximately 2 mL/min. During 14 days after the injection, general symptoms were observed and weight were measured. After the observation period, hematological and blood biochemical examination, macroscopic autopsy, topical resistance test at the injection area were performed. Results: RThe WDP 0.5 mL/animal injection group in 4 cases of male rats and all cases of female rats showed hematuria 30 minutes after the administration. However, after 1 hour, no more abnormal general symptoms were observed. The WDP did not affect weight, hematological and blood biochemical examination, macroscopic autopsy, and topical resistance test at the injection area. Conclusion: WDP single dose intravenous injection results showed that WDP have no toxic effects and a lethal dose of WDP should be over 0.5 mL/animal in male and female rats under the study condition. So WDP may be safe.